Eritrea: Recent developments in agricultural research - Rahija, Michael; Fesha, Iyassu; Stads, Gert-Jan (International Food Policy Research Institute, 2010)
When Eritrea achieved independence from Ethiopia in 1993 after a long war, the country's economy was in ruins, and public infrastructure and institutions were seriously damaged or destroyed. The new government faced a long process of establishing public-sector organizations to stimulate economic growth and provide basic services. Strengthening national agricultural research and development (R&D) and extension services was high on the list of priorities. In the first years after independence, the country's agricultural output, as well as its agricultural R&D expenditures, rose rapidly following an influx of support from foreign donors. Nevertheless, renewed conflict with Ethiopia in 1998 led to dramatic cuts in funding from both donors and the national government (Beintema, Okubay, and Debass 2003). In 2008, Eritrea invested 11.7 million nakfas or 1.9 million PPP dollars (in 2005 prices) in agricultural R&D, down from 90 million nakfas or 14 million PPP dollars a decade earlier, which represents a drop of 80 percent.